Optimizing Learning: Adaptive Technology Integration in Indonesia's Education System - Agustina, Rika Hasmayanti; Alfiyanto, Afif; Suhendri, Suhendri; Wihardjo, Edy; Pranajaya, Syatria Adymas (Jurnal Ilmu Pendidikan (JIP) STKIP Kusuma Negara, 2025)
Adaptive technology in education offers an innovative solution to enhance learning quality by personalizing instructional materials according to students’ needs. This study aims to analyze the potential of adaptive technology in Indonesia’s education system and identify its implementation challenges. Using a literature review method, this research examines various studies on the application of adaptive technology in education, particularly within the "Merdeka Belajar" framework. The findings indicate that adaptive technology can enhance student engagement, facilitate data-driven learning, and assist teachers in accurately identifying student difficulties. However, major challenges in its implementation include limited infrastructure, gaps in digital literacy among educators, and cultural resistance to technology in education. To address these barriers, strategic measures such as strengthening digital infrastructure, implementing TPACK-based teacher training, and educating communities about the benefits of adaptive technology are necessary. With these recommendations, adaptive technology is expected to be effectively integrated into Indonesia’s education system, fostering more inclusive, flexible, and high-quality learning.